Comparative Analysis of Indicators of Coordination Abilities Development in 5th-7th Graders - В. В. Приходько (OVS LLC, 2017)
The objective of the research is to determine the regularities of coordination abilities development in 5th-7th-grade boys.  Materials and methods. The participants in the research were boys of the 5th grade (n = 21), 6th grade (n = 20), 7th grade (n = 19). To achieve the tasks outlined, the research used the following methods: analysis of scientific and methodological literature; pedagogical testing, pedagogical observation, methods of mathematical statistics. Research results. The 5th-6th-grade boys show a statistically significant difference between their results in the following tests: "Standing long jump (cm)" (p < 0.002); "Six standing accuracy ball handlings to a partner from a 7 m distance using one of the techniques learned" (p < 0.049); "Rhythmic hand tapping" (p < 0.044); "Rhythmic movements of upper and lower limbs" (p < 0.042) (p < 0.05); "Height (cm)"; "Body weight (kg)". The 6th-7th-grade boys - "30 m running (s)"; "Standing long jump (cm)"; "Sit-ups in 30 seconds"; "Evaluation of static equilibrium by E. Ya. Bondarevsky's method"; "Evaluation of dynamic equilibrium by the BESS method"; "Rhythmic hand tapping"; "Rhythmic movements of upper and lower limbs"; "Shuttle run (4 × 9 m)"; "Tossing rings over a peg". The 5th-7th-grade boys - "Standing long jump (cm)"; "Pull-ups (number of times)"; "Evaluation of the ability to differentiate movement speed (accuracy in reproduction of running speed, 90% of maximum)"; "Evaluation of static equilibrium by E. Ya. Bondarevsky's method"; "Evaluation of dynamic equilibrium by the BESS method"; "Rhythmic hand tapping"; "Shuttle run (4 × 9 m)"; "Height (cm)"; "Body weight (kg)". Conclusions. The research has observed a positive dynamics of the results in the following group of tests: "Standing long jump" by 8.4%, "Rhythmic hand tapping and rhythmic movements of upper and lower limbs" by 18.5% and 17.5%, respectively, "Height" by 6.2% (5th-6th grades); "30 m running (s)" by 0.2%; "Standing long jump" by 6.9%; "Static equilibrium" by 43.7%; "Tossing rings over a peg" by 17.5% (6th-7th grades); "Standing long jump" by 15.8%, "Pull-ups" by 48.1%, "Evaluation of the ability to differentiate movement speed (accuracy in reproduction of running speed, 90% of maximum)" by 26.7%; "Evaluation of static equilibrium by E. Ya. Bondarevsky's method" by 58.4%; "Height (cm)" by 9.7%; "Body weight (kg)" by 47.1%. (5th-7th grades).